KAJIAN HUKUM ISLAM TERHADAP DINAMIKA PELAKSANAAN ZAKAT PADI: (Studi Di Kampung Sukajadi Kecamatan Bumiratu Nuban) - Muhklisin, Ahmad (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2016)
Islam is a comprehensive doctrine that recognizes indifidu rights and collective rights of communities simultaneously, in Islam recognizes differences in income and wealth in every person with a condition that is caused due to the difference erbedaan skills, initiative, effort and risk. Given such case, the group comes the rich and the poor. Then to stabilize such things related to Islam provides solutions together, helping each other and equally feel that the presence of Zakat. Zakat is one tool that can be relied upon for the equitable distribution of income in the achievement of economic justice, thereby reducing poverty, the main objective of zakat is to eradicate poverty, with the hope of changing their recipients of zakat (Mustahik) into paying Zakat (muzakki) rehingga empowerment and equitable distribution of zakat become more meaningful. According to the results of the implementation of the pre-survey zakat different kampong rice no zakat issued immediately after harvest without capital is calculated and others cut harvests in advance with the needs of the farmer and then a new release of zakat. This is important to investigate according to the researchers then linked with Islamic law and the law presented to the community for charity is not felt heavy for farmers. The problem of this first article How is the implementation of Zakat kampong rice Sukajadi excl. Bumiratu Nuban? Secondly How Islamic legal view of the implementation of zakat rice in the village?